Islet amyloid polypeptide & amyloid beta peptide roles in Alzheimer's disease - Ferreira, Sofia (2020)
Funding: This work was supported by iNOVA4Health – UID/Multi/04462/2019, a program financially supported by Fundação para a Ciência e Tecnologia/ Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement, Funding from INTERFACE Programme, through the Innovation, Technology and Circular Economy Fund (FITEC), FCT via PTDC/BIA-MOL/31104/2017 and UID/Multi/04462/2019-SubProj iNOVA4Health C44 (to RM), PD/BD/135504/2018 (to AFR), Sociedade Portuguesa de Diabetologia for the Nuno Castelo-Branco Prize – 2016 (to RM), and ICM acknowledges FCT-MCTES Program “Concurso de Estímulo ao Emprego Científico” (CEECIND/01670/2017).